Comparison of QT interval variability of coronary patients without myocardial infarction with that of patients with old myocardial infarction. (October 2019) - Yao, Lianke; Li, Peng; Liu, Changchun; Hou, Yunxiu; Yan, Chang; Li, Liping; Li, Ke; Wang, Xinpei; Deogire, Aruna; Du, Chunlei; Zhang, Huan; Wang, Jikuo; et al.
Abstract: Background: The significant association of myocardial ischemia with elevated QT interval variability (QTV) has been reported in myocardial infarction (MI) patients. However, the influence of the time course of MI on QTV has not been investigated systematically. Method: Short-term QT and RR interval time series were constructed from the 5 min electrocardiograms of 49 coronary patients without MI and 26 patients with old MI (OMI). The QTV, heart rate variability (HRV), and QT–RR coupling of the two groups were analyzed using various time series analysis tools in the time- and frequency-domains, as well as nonlinear dynamics. Results: Nearly all of the tested QTV indices for coronary patients with OMI were higher than those for patients without MI. However, no significant differences were found between the two groups in any of the variables employed to assess the HRV and QT–RR coupling. All of the markers that showed statistical significances in univariate analyses still possessed the capabilities of distinguishing between the two groups even after adjusting for studied baseline characteristics, including the coronary atherosclerotic burden. Conclusions: The results suggested that the QTV increased in coronary patients with OMI compared to those without MI, which might reflect the influence of post-MI remodeling on the beat-to-beat temporal variability of ventricular repolarization. The non-significant differences in the HRV and QT–RR couplings could indicate that there were no differences in the modulation of the autonomic nervous system and interaction of QT with the RR intervals between the two groups. Highlights: The QTV increased in coronary patients with OMI compared to those without MI. Elevated QTV might reflect the influence of post-MI remodeling. The HRV and QT–RR couplings showed no differences between the two groups.